Effect of Range of Motion on Muscle Strength in Stroke Patients At Mokopido Tolitoli Hospital: Pengaruh Range of Motion Terhadap Kekuatan Otot Pasien Stroke Di RSUD Mokopido Tolitoli - Novica Ariyanti Putri; Rizkaningsih Rizkaningsih (Salando Health Journal, 2025)
Stroke is one of the leading causes of disability, resulting in muscle weakness and limited mobility. Range of Motion (ROM) exercises are a physiotherapy intervention that can improve muscle strength in stroke patients. This study aims to analyze the effect of ROM exercises on muscle strength improvement in stroke patients at Mokopido Tolitoli Regional Hospital. This study used a pre-experimental design with a one-group pretest-posttest approach without a control group. The study sample consisted of 10 stroke patients with muscle weakness. Muscle strength was measured using Manual Muscle Testing (MMT) before and after ROM exercises, which were conducted for two weeks with a frequency of five sessions per week. Data were analyzed using the paired t-test to determine differences in muscle strength before and after the intervention. The results showed a significant increase in MMT scores after ROM exercises (p < 0.05). Before the intervention, most patients had muscle weakness with an average MMT score of 2.1 ± 0.7, while after ROM exercises, the average score increased to 3.8 ± 0.6. The paired t-test result showed a value of t = -6.89; p = 0.001, indicating that ROM exercises had a significant effect on improving muscle strength in stroke patients. ROM exercises are effective in increasing muscle strength in stroke patients. Implementing ROM exercises in stroke rehabilitation programs can help prevent muscle atrophy, improve mobility, and accelerate motor function recovery. Further research with a larger sample and a more robust study design is needed to confirm these findings.